Impact of Different Degrees of Uterine Prolapse on Sexual Function of Women at Teaching Hospitals in Al-Hilla City - Hashim, ghada; ALdeen, Ezedeen (Iraqi National Journal of Nursing Specialties, 2015)
Background: Women sexuality is basic right and it plays a major role in women’s Health aspects. Up is one of the factors that lead to sexual dysfunction while the incidence of it is rising as UP severity being more. Objectives: To assess the impact of different degrees of uterine prolapse on sexual function of women at teaching hospitals in AL-Hilla City. Methodology: A descriptive analytical study was conducted from 1ST Feb to 10th Jun /2014 to assess the impact of different degrees of uterine prolapse on sexual function for women who attend to consultant clinic at teaching hospitals in AL-Hilla City. Result: The result show the highest percentage was 46% of the study group were at age group range(35-44)yrs.,62% work as employment ,22% housewives ,40% have second degree of prolapse ,37% have first degree and 23% have third degree there is no symptoms at first degree or simple but it is being more severe when the degree of prolapse increased,58% have no sexual desire,60% have no orgasm ,74% have no exciting,75% have no satisfaction. Recommendations: result finding indicate to necessity for women awareness program at reproductive age about UP and factors that lead to it and its complications which the sexual dysfunction was one of them.